1998
DOI: 10.1080/09540109809354977
|View full text |Cite
|
Sign up to set email alerts
|

Development of high‐sensitive enzyme immunoassays for gliadin quantification using the streptavidin‐biotin amplification system

Abstract: Optimization of three enzyme immunoassays of very high sensitivity using three antiprolamin monoclonal antibodies (MAbs) (13B4, 11C4 and 12A1) is presented here. These MAbs are specific for those prolamins toxic for coeliac patients, as determined by immunoblotting analysis. Biotinylated MAbs were used in two of the assays. In a competitive ELISA, the binding of each biotinylated MAb to a gliadin-coated solid phase was inhibited by gliadin in the fluid phase. The best result was obtained using the biotinylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Furthermore, with the exception of one ELISA based on the use of three monoclonal antibodies [4], most methods are incapable of detecting wheat, rye and barley prolamins equally effectively [5][6][7]. Today's ELISAs based on monoclonal antibodies need to show a wider specificity towards prolamins toxic to coeliac patients, along with a higher degree of sensitivity, accuracy and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with the exception of one ELISA based on the use of three monoclonal antibodies [4], most methods are incapable of detecting wheat, rye and barley prolamins equally effectively [5][6][7]. Today's ELISAs based on monoclonal antibodies need to show a wider specificity towards prolamins toxic to coeliac patients, along with a higher degree of sensitivity, accuracy and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…MAbs were purified from ascites by affinity chromatography in a protein A‐Sepharose column (Pharmacia). One MAb (Rye 3), which recognized gliadins, secalins, hordeins and avenins in direct ELISA and immunoblotting (see below), was conjugated to HRP by using the periodate method [16].…”
Section: Methodsmentioning
confidence: 99%
“…According to previous results, the eVect of denaturating agents appears to depend on the antibody and ELISA format employed. Therefore, we extended the analysis by assessing the combined eVect of 2-ME and GuHCl in competitive and capture ELISAs using diVerent antibody systems [38]. Altogether, these studies allow assessment of the eVects of 2-ME and GuHCl As reported for several proteins, 2-ME and GuHCl produce conformational changes leading to a decrease in the biological activity.…”
Section: Discussionmentioning
confidence: 94%
“…Capture ELISAs were developed using pairs of diVerent anti-gliadin monoclonal antibodies (mAbs) prepared by our group. 1B4E9 or 3B4H1 mAbs were used for antigen capture and biotinylated 2A1C4 or 1B4E9 mAbs were used as detection antibodies following the procedure described elsewhere [38]. BrieXy, plates were coated overnight at 4 °C with 1B4E9 or 3B4H1 mAb in PBS.…”
Section: Capture Elisasmentioning
confidence: 99%